New approach to mastoid asymmetry (Annals of Medical Research, 2022)
Aim: To indicate the association between chronic otomastoiditis (COM) and the asymmetry in mastoid length and pneumatization.Materials and Methods: 1.870 patients who underwent computed tomography (CT) imaging for various indications were retrospectively evaluated. Of the 1.870 patients, 67 were included in this study. Coronal and sagittal images of 67 patients were evaluated and 3D reconstructed.Results: There was no significant difference in age or gender between right and left side hypopneumatization (p>0.05).Thevertical length  difference between the tips of mastoids (VLBM)  was significantly higher in patients with left hypopneumatized mastoid than the right ones (p
Keywords: Mastoid asymmetry; Chronic otomastoidit; Computed tomography (CT)